The Impact of Dhuha Prayer on the Formation of Religious Behavior of Class V Students at Mi Mq. An-Nuur - Nurfitriyani; Endah Robiah Adawiyah; Siti Umi Hani (Indonesian Journal of Educational Science and Technology, 2023)
This research is motivated by the role of the madrasah institution which not only creates outstanding individuals but also has an Islamic spirit. Institutions need to make improvements in the field of religious education in addition to general education. The Islamic generation that is expected in the future will have high science and technology and strong IMTAQ, so that later they will have strong competitiveness. Therefore, madrasas not only teach theories of subject matter, but also provide Islamic teachings to shape students' religious behavior, one of which is by holding dhuha prayers. Because whoever istiqomah to perform the Duha prayer will be facilitated and his sustenance will be facilitated. The purpose of this study was to find out how the impact of the habituation of the Duha prayer has on the formation of students' religious behavior. This research was conducted at Mi Mq. An-Nur. In this study used the method of observation and interviews, in order to obtain data. After the researchers conducted research using several of the methods above, the results showed that there was an impact on the habituation of Duha prayer on students' religious behavior, this was evidenced by the routine activities of Duha prayer in congregation every morning before the learning process began. The impact of this dhuha prayer is that it forms students into caring behavior for others, likes to help, and respects their elders.